Measuring real activity using a weekly economic index - Daniel J. Lewis; Karel Mertens; James H. Stock; Mihir Trivedi (Federal Reserve Bank of New York, 2020)
This paper describes a weekly economic index (WEI) developed to track the rapid economic developments associated with the onset of and policy response to the novel coronavirus in the United States. The WEI is a weekly composite index of real economic activity, with eight of ten series available the Thursday after the end of the reference week. In addition to being a weekly real activity index, the WEI has strong predictive power for output measures and provided an accurate nowcast of current-quarter GDP growth in the first half of 2020. We document how the WEI responded to key events and data releases during the first six months of the pandemic.
Keywords: C51; E01; E66; 330; weekly economic index; high frequency; measurement of economic activity; forecasting; Coronavirus; Epidemie; Wirtschaftsindikator; Frühindikator; Konjunktur; USA